A partir du 31 Janvier 45.000 réfugiés hongrois en Autriche seront pris en charge par la Croix-Rouge . 45,000 Hungarian Refugees in Austria to be Receiving Red Cross Maintenance and Care Services by January 31 - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): League of Red Cross Societies